CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE PRACTICES AND OWNERSHIP - Sharma, Jeevesh; Verma, Dr. Suhasini (The journal of contemporary issues in business and government, 2021)
The study aims to analyze whether the firm’s ownership has any impact on their corporate social responsibility (CSR) expenditure pattern and disclosure practices. The study also examines CSR schedule and CSR expenditure covered by public and private sector firms over the years and marks the differences in the pattern of CSR disclosure. The paper is descriptive and analytical and draws its sample from S&P BSE Carbonex firms. Data has been collected through secondary sources which include the firm’s websites, annual reports, Prowess IQ database, and CSR database (NSE Infobase). The findings of the study may help the management to recognize which CSR activities are being neglected and also assist policymakers in devising policies to improve the level of disclosure and transparency in CSR activities. The findings show that some firms are highly focused on education and health- related activities and less focused on areas such as war veterans, disaster management, protection of flora and fauna, and sports.